Loneliness among seniors - Natalia Skierkowska; Weronika Topka; Małgorzata Kwiatkowska; Monika Prylińska (Kazimierz Wielki University, 2020)
Introduction: Loneliness is a universal phenomenon that affects people of any age. But it becomes especially painful for people over 60 years of age. Loneliness makes seniors vulnerable to isolation and marginalization. Aim: The aim of the article is to present the topic of loneliness among the elderly. Material and methods: The article analyzes the current literature from EBSCO and Google Scholar websites. The keywords used are: loneliness, elderly, loneliness, senior. Results: Loneliness is one of the greatest problems of the modern world. There are many causes of loneliness from geographic factors to loneliness caused by illness. The factor determining loneliness is the conscious withdrawal of seniors from activity due to, for example, their disability. Conclusions: Loneliness and loneliness contribute to the deterioration of the quality of life of seniors.